On the structure of solutions of a system of singularly perturbed differential equations with nondiagonalizable limit operator - Bobochko, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We construct uniform asymptotics of a solution of a heterogeneous system of singularly perturbed differential equations in the case of nondiagonalizable limit operator. We consider the case where the spectrum of the limit operator contains an unstable element at the point x = 0.